2016
DOI: 10.1172/jci80046
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding protein IGF2BP3 targeting of oncogenic transcripts promotes hematopoietic progenitor proliferation

Abstract: Posttranscriptional control of gene expression is important for defining both normal and pathological cellular phenotypes. In vitro, RNA-binding proteins (RBPs) have recently been shown to play important roles in posttranscriptional regulation; however, the contribution of RBPs to cell specification is not well understood. Here, we determined that the RBP insulin-like growth factor 2 mRNA-binding protein 3 (IGF2BP3) is specifically overexpressed in mixed lineage leukemia-rearranged (MLLrearranged) B-acute lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
197
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(206 citation statements)
references
References 64 publications
(70 reference statements)
9
197
0
Order By: Relevance
“…In control experiments, treatment of adult progenitors with BET inhibitors failed to upregulate the cytoskeletal remodeling factors or HEXIM1, failed to induce RNAPII hyperphosphorylation, and did not induce cellular enlargement (Supplemental Figure 11, C-E). During the preparation of this manuscript, Palanichamy et al also showed repression of IGF2BP3 expression by BET inhibition (36).…”
Section: Bet Factor Regulation Of Igf2bp3 Enables Pharmacologic Modulmentioning
confidence: 82%
“…In control experiments, treatment of adult progenitors with BET inhibitors failed to upregulate the cytoskeletal remodeling factors or HEXIM1, failed to induce RNAPII hyperphosphorylation, and did not induce cellular enlargement (Supplemental Figure 11, C-E). During the preparation of this manuscript, Palanichamy et al also showed repression of IGF2BP3 expression by BET inhibition (36).…”
Section: Bet Factor Regulation Of Igf2bp3 Enables Pharmacologic Modulmentioning
confidence: 82%
“…Although IMP1 and IMP3 may also bind to MREs or in their immediate vicinity, safe-housing transcripts in a RISC-free environment constituted of mRNP granules is currently the best-understood mechanism by which they protect their target mRNAs. lymphoid-primed multipotent progenitors (LMPPs), and common lymphoid progenitors (CLPs) in the bone marrow, with increased proliferation of HSCs and LMPPs (Palanichamy et al 2016). Mouse hematopoiesis was skewed toward the myeloid and B-cell lineages accompanied by leukocytosis in the peripheral blood, atypical infiltration of B cells into the thymic medulla, and increased myeloid cell numbers in the spleen (Palanichamy et al 2016).…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
“…lymphoid-primed multipotent progenitors (LMPPs), and common lymphoid progenitors (CLPs) in the bone marrow, with increased proliferation of HSCs and LMPPs (Palanichamy et al 2016). Mouse hematopoiesis was skewed toward the myeloid and B-cell lineages accompanied by leukocytosis in the peripheral blood, atypical infiltration of B cells into the thymic medulla, and increased myeloid cell numbers in the spleen (Palanichamy et al 2016). The observed phenotype was ascribed to stabilization of Myc and Cdk6 mRNAs by IMP3 based on individual nucleotide-resolution CLIP (iCLIP) analysis and reporter assays.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Igf2bp3 is an important member of a critical upstream signalling pathway that drives cell proliferation (Ennajdaoui et al, 2016;Lederer et al, 2014, Chernoff, 1999. In particular, Igf2bp3 (Palanichamy et al, 2016;Schaeffer et al, 2010) and Ube2c (Bajaj et al, 2016;Chou et al, 2014;Shen et al, 2013;Shuliang et al, 2013) have been widely studied in various cancers, confirming their ability to promote cell proliferation. Interestingly, their expression levels are substantially down-regulated during postnatal cardiac development.…”
Section: Resultsmentioning
confidence: 99%